Immersive Technology-Based Adaptive Learning to Improve Academic Achievement and Interpersonal Skills in Electrical Engineering Education - Adha, Hanif Rifai; Rahmawati, Yuni; Wibowo, Danang Arengga; Masyfa, Faiz Hilmawan (DPTE FT UNY, 2026)
The Development of digital technology creates significant opportunities to improve the learning experience in the engineering education sector. This study investigates and analyses the impact of Augmented Reality as an immersive learning technology to improve academic achievement and interpersonal skills (collaboration and communication). A quasi-experimental design was used to compare the influence of AR-based learning with conventional learning systems in two classes of 60 students. Pre-test and post-test results showed significant improvement in the experimental class, with paired t-tests showing mean differences of -31.20 (t = -20.75, p < 0.001) and -18.76 (t = -13.67, p < 0.001) for the control class. A greater improvement in collaboration and communication skills was observed in the experimental class compared to the control class. The t-test independently revealed significant differences in collaboration skills (t = 4.92, p < 0.000) and communication skills (t = 2.71, p < 0.000). AR provides a more interactive learning experience, improving teamwork and effective communication. These results demonstrate that AR has significant potential in enhancing academic capabilities and 21st-century skills in engineering education.